The Changes of Serum Inflammatory Cytokines in Patients with Hemiplegia after Ischemic Stroke and the rehabilitation effects: TNF-α, hs-CRP, IL-6, IL-18 in Hemiplegic Patients - Lai, Yunqi (Journal of Medical Biochemistry, 2025)
Introduction: The aim of this article was to explore the rehabilitation effects of early precision exercise rehabilitation on patients with hemiplegia due to acute ischemic stroke (AIS) and its effect in improving neurological function, motor ability, and self-care in daily life and to assess the impact of early treatment on the levels of patients’ inflammatory factors (such as TNF-α, hs-CRP, IL-6, IL-18), to further understand its potential mechanisms on neural repair and rehabilitation outcomes Material and Method: A retrospective inclusion of 230 patients with hemiplegia due to AIS was conducted, and the patients were grouped: early group (EG, 132 cases) and conventional group (CG, 98 cases) based on different treatment plans. The EG received an early exercise rehabilitation training program; the CG received traditional rehabilitation training. The effectiveness before and after treatment was assessed by the national institutes of health stroke scale (NIHSS) scoring, Wisconsin gait scale (WGS) scoring, activities of daily living (ADL) scoring, joint and muscle function indicators, and serum inflammatory factors. Result: The EG suggested visibly better NIHSS scoring, WGS scoring, ADL scoring, walking frequency, walking speed, and joint mobility following interference compared to the CG; no visible distinction was noted in the serum inflammatory factor levels of the subjects before intervention (P >0.05). Following interference, the serum inflammatory factor levels in the EG were obviously lower as against the CG (P <0.05). Conclusion: Early precision exercise rehabilitation can visibly improve the neurological function, motor ability, and self-care ability of patients with hemiplegia due to AIS and effectively suppress inflammatory responses, promoting neural repair.